Súmula vinculante: um novo controle de constitucionalidade - Pelicani, Rosa Benites (2007)
The Amendment no. 45 to the Constitution, enacted on December 8th, 2004, regarding the Reform of the Judiciary Power, introduced article 103-A to the Federal Constitution of 1988, which provides for the binding effect of Abridgments of Law issued by the Brazilian Supreme Court. Several voices still make themselves heard, some in favor and some against such binding effect, based on various arguments, such as the slowness of courts, the access to them, the freedom to judge, the role of the jurisprudence, and the regulatory power of such abridgments. The matter can, however, be viewed from a new perspective. Given the supremacy of the Federal Constitution, and since the subject of a binding decision is a constitutional matter, a new constitutionality control is envisaged in the new binding effect. But some questions are asked: could an amendment to the constitution introduce yet another form of control? Why would binding decisions be a kind of control? This paper, making reference to renowned legal scholars, sets off on the journey with remarks on language and concepts, approaches history and the foreign law in a simple fashion, and seeks to answer these and other questions that came up in the course of its preparation, while bringing reflections on the regulation of article 103-A of the Federal Constitution, under Law no. 11,417, enacted on December 19th, 2006